FRI0304 SERUM IGG-UNDERGALACTOSYLATION PROFILES REFLECT CUMULATIVE EXPOSURE TO SYSTEMIC INFLAMMATION IN SPONDYLOARTHRITIS PATIENTS. (2nd June 2020) - De Craemer, A. S.; Lukasik, Z.; Meuris, L.; Deroo, L.; Renson, T.; De Hooge, M.; Carron, P.; Van Hecke, A.; Callewaert, N.; Van den Bosch, F.; Elewaut, D.
Abstract : Background: Inflammation in spondyloarthritis (SpA) is often not reflected by elevated acute phase reactants such as C-reactive protein (CRP) or erythrocyte sedimentation rate (ESR). It has been shown that IgG glycosylation patterns are subject to specific alterations (i.e. undergalactosylation) in chronic inflammatory diseases. Since these changes only occur in persistent inflammatory processes, lasting at least one to two t1/2 of IgG (24 days), it was hypothesized that IgG-glycan profiles could serve as a surrogate marker for chronic inflammation in SpA patients. Objectives: To assess the value of serum IgG-undergalactosylation in SpA patients in relation to outcome measures for disease activity, determined by patient reported outcomes, serum inflammatory markers and imaging outcomes. Methods: Serum samples were obtained from SpA patients at the baseline visit of Be-Giant: a Belgian observational cohort including SpA patients who fulfill the ASAS classification criteria for axial or peripheral SpA. IgG Fc N-glycans were released directly in whole serum by endo-β-N-acetyl-glucosaminidase from Streptococcus pyogenes (EndoS), fluorescently labeled with ATPS and analyzed by capillary electrophoresis, rendering glycan profiles with six peaks (Figure 1 ). Relative peak heights were combined in the undergalactosylation score (UGS), capturing the relative upregulation of non-galactosylated glycans normalized to the total peak height (1). Baseline radiographs (X-SIJ) and magnetic resonance images (MRI) of the sacroiliac joints (SIJ) were assessed by three calibrated readers for sacroiliitis (fulfillment of the modified New York criteria; grading 0 to 4 per SIJ) and for inflammatory lesions according to the Spondyloarthritis Research Consortium of Canada (SPARCC) method (score from 0 – 72) respectively. Grades and inflammatory lesions that were seen by at least 2 readers were used for further analysis. Results: Glycan profiles were obtained from 376 SpA patients; UGS was scaled (mean = 0, SD = 1) for further analysis. UGS was independently associated with ASDAS-CRP (β1 = 0.15, 95% CI 0.04 – 0.26, p = 0.006) and BASFI (β1 = 0.44, 95% CI 0.16 – 0.72, p = 0.002) but not with BASDAI (β1 = 0.12, 95% CI -0.13 – 0.38, p = 0.34). UGS showed a weak to moderate correlation with CRP (Rs = 0.30, p < 0.001) and ESR (Rs = 0.27, p <0.001). In axial SpA, UGS was significantly higher in patients with ankylosing spondylitis compared to non-radiographic axial SpA (OR = 2.41, 95% CI 1.60 – 3.73, p < 0.001) and showed an independent association with the total grading of the SIJ (β1 = 0.44, 95% CI 0.09 – 0.80, p = 0.01, Figure 2 ) and SPARCC score (β1 = 2.64, 95% CI 0.98 – 4.31, p = 0.002). All models were adjusted for age, gender, BMI, CRP, anti-TNF treatment and symptom duration. Conclusion: This study shows and independent association of serum IgG undergalactosylation with disease activity and functional impairment in SpA patients. Moreover, UGS was significantly higher in advanced compared to early-stage axial disease and therefore may reflect the cumulative exposure to systemic inflammation. References: [1]Vanderschaeghe D, Meuris L, Raes T, et al. Endoglycosidase S Enables a Highly Simplified Clinical Chemistry Procedure for Direct Assessment of Serum IgG Undergalactosylation in Chronic Inflammatory Disease. Mol Cell Proteomics. 2018;17(12):2508-17. Disclosure of Interests: Ann-Sophie De Craemer: None declared, Zuzanna Lukasik: None declared, Leander Meuris: None declared, Liselotte Deroo: None declared, Thomas Renson: None declared, Manouk de Hooge: None declared, Philippe Carron: None declared, Annelies Van Hecke: None declared, Nico Callewaert: None declared, Filip van den Bosch Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Dirk Elewaut: None declared